O Museu de Arte de Belém em tempos de pandemia e suas redes sociais (Facebook e Instagram) - SOUSA, Suellen Oliveira (2023)
The work is based on the collection of information from the social networks of the Museu de Arte de Belém (Facebook and Instagram) between May 2019 and July 2021, in the periods before the onset of the COVID-19 pandemic and after the loosening of restrictions caused by the pandemic. With the objective of establishing comparison parameters of MABE's museum practices in their social networks. The methodologies adopted during the research were the bibliographic and qualitative and quantitative research. And to complement the information collected on MABE's social networks, conversations were held, with structured questions for two employees of the institution. The results show that the profiles of the publications changed according to several events that occurred due to the increase in COVID-19 cases in Belém and due to the period of revitalization works at the museum's headquarters. By keeping the museum's social networks dynamic, bringing information about events and exhibitions, it allowed a significant reach for people to know more about the museum and its collection.